Description of Microbial Communities of Phosphate Mine Wastes in Morocco, a Semi-Arid Climate, Using High-Throughput Sequencing and Functional Prediction - Mghazli, Najoua; Sbabou, Laila; Hakkou, Rachid; Ouhammou, Ahmed; El Adnani, Mariam; Bruneel, Odile (Frontiers in Microbiology, 2021)
Soil microbiota are vital for successful revegetation, as they play a critical role in nutrient cycles, soil functions, and plant growth and health. A rehabilitation scenario of the abandoned Kettara mine (Morocco) includes covering acidic tailings with alkaline phosphate mine wastes to limit water infiltration and hence acid mine drainage. Revegetation of phosphate wastes is the final step to this rehabilitation plan. However, revegetation is hard on this type of waste in semi-arid areas and only a few plants managed to grow naturally after 5 years on the store-and-release cover. As we know that belowground biodiversity is a key component for aboveground functioning, we sought to know if any structural problem in phosphate waste communities could explain the almost absence of plants. To test this hypothesis, bacterial and archaeal communities present in these wastes were assessed by 16S rRNA metabarcoding. Exploration of taxonomic composition revealed a diversified community assigned to 19 Bacterial and two Archaeal phyla. The dominant sequences belonged to Proteobacteria, Bacteroidetes, Actinobacteria and Gemmatimonadetes and to the genera Massilia, Sphingomonas, and Adhaeribacter. LEfSe analysis identified 19 key genera and metagenomic functional prediction revealed a broader phylogenetic range of taxa than expected, with all identified genera possessing at least one plant growth-promoting trait. Around 47% of the sequences were also related to genera possessing strains that facilitate plant development under biotic and environmental stress conditions, such as drought, heat, etc.